Needs Analysis of A JOYDATA–STEAM Approach for Data Literacy in Statistics - Elfa Mawadati; Nizaruddin; Muhtarom (JTP - Jurnal Teknologi Pendidikan, 2026)
Low levels of data literacy and students’ reasoning skills in statistics remain a major challenge in senior high school mathematics education. Procedural and decontextualized instructional practices have limited students’ engagement in meaningful data analysis activities. This study aims to analyze the needs of students and teachers as a foundation for developing a JOYDATA–STEAM learning model using a design thinking approach up to the ideate phase. A descriptive research method was employed, and data were collected using questionnaires distributed to senior high school students and teachers. The findings indicate that students prefer learning experiences involving real-world data, data visualization, simple project-based activities, and the use of digital media. Meanwhile, teachers reported a gap between current instructional practices and the need to develop students’ higher-order reasoning skills and data literacy. Based on the empathize and define stages, key instructional needs were identified, which informed the ideate stage in generating initial concepts for the JOYDATA–STEAM learning model. This model positions data literacy as a core component of learning, encompassing data collection, processing, visualization, and interpretation in a structured and progressive manner. These findings contribute to the development of an integrative and data-driven statistics learning model that supports student engagement and addresses the demands of 21st-century education.